PROFIL PASTING PATI GANYONG TERMODIFIKASI DENGAN HEAT MOISTURE TREATMENT DAN GUM XANTHAN UNTUK PRODUK ROTI - - Parwiyanti; Filli Pratama; Agus Wijaya; Nura Malahayati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
The purpose of this study was to determine the pasting properties of modified canna starch produced with heat moisture treatment (HMT) and addition of xanthan gum (XG) for gluten free bread. This research used a Factorial Randomized Completely Design with two factors as treatments for pasting properties and one factor of starch’s type for bread dough formulation. The first factor (A) was HMT temperatures (80 and 100oC) for 8 hours at canna starch water content of 15% and the second (C) was the concentration of XG (0; 0.5; 1; 1.5; 2% w/w). The parameters determined were pasting properties and specific volume, texture, and sensory analysis for bread. The results showed that all treatments and their interaction had significant effect on the pasting properties, while XG concentration had no significant effect on the gelatinization time. Meanwhile, interaction between HMT temperatures and XG concentration had no significant effect on the setback. The best treatment was canna starch modified by HMT at 80oC and added with 1.5% of xanthan gum, with 72.25±0,23oC of gelatinization temperature; 6.16±0.04 minutes of gelatinization time, 4556±107.01 cP of peak viscosity, 5141±64.00 cP of final viscosity, 2235±27.51 cP of breakdown, and 2818±15.52 cP of setback. The specific volume of the bread produced was 2.85±0.017 cm3/g, texture of 109.03±7.50 gf and average hedonic scores for taste, color, texture and aroma of 5.34; 5.46; 5.56 and 5.80 respectively (5=least liked, 6=liked).